MAPEAMENTO DA PERCEPÇÃO DOS ALUNOS DE UMA ESCOLA DE IDIOMAS: UMA ADAPTAÇÃO AO MODELO HEdPERF - Chagas, Leila Rodrigues (2009)
In a highly competitive market, providing quality services is essential to the survival and success of companies. In the education market, this competitiveness is not different, thus rendering it necessary to captivate the students perception of the quality of the service provided, so that any possible improvements may be carried out safely and effectively. Various models have been created to evaluate the quality of services, such as the Gap Model, the SERVQUAL Scale, SERVPERF Model and the HEdPERF Model. The Gap model, the SERVQUAL Scale and the SERVPERF Model are said to be generic, which means, applicable to any type of service. However, the HEdPERF model was developed specifically to evaluate the quality of Higher Education Institutions. The main goal of this dissertation is to study the application of the HEdPERF Model in evaluating students perception in relation to the quality of services provided by a language school in light of the five dimensions of quality; academic aspects, non-academic aspects, Content Standards, accessibility, reputation. Thus, we developed one adaptation to the HEdPERF questionnaire in order to evaluate the perception of students in relation to one school of such field of activity in the city of Juiz de Fora, Brazil. The data collected were analyzed using descriptive statistical analysis containing frequency tables, Bar Graphs, sectors and measures such as medium and standard deviation. An analysis of correlation through Spearman s rho was conducted to verify the correlation between the 41 variables related to attributes that comprise the five dimensions of quality with the dependable variable which evaluates the general satisfaction with the school. All analysis was carried out with the help of the software SPSS (Statistical Package for the Social Sciences) V. 15.0. The application of the questionnaire adapted from the HEdPERF model enabled us to identify the aspects of possible improvement to be prioritized through the analysis of students perception in a study of performance and the importance of all the attributes that compose the five dimensions of quality. It also made possible to identify the attributes which possess a correlation with the level the student s satisfaction with the school.